Quantification of microstructural damage in asphalt - Khan, Rawid (2010)
This research is concerned with quantifying damage in asphalt mixtures at the micro level. X ray Computer Tomography (CT) a non destructive technique along with image analysis has been used to study the internal microstructural properties of asphalt.